Development of Hydrographic Risk Assessment in Planning Hydrooceanographic Survey and Charting Areas - Alin Abimanyu; Heru Syamsul Hidayat; M. Asrof Widiarto (Publikasi Indonesia, 2025)
As an archipelagic country, Indonesia faces significant challenges in ensuring maritime safety and conducting effective hydrographic surveys. The Hydrographic Risk Assessment (HRA) approach is used to identify high-risk areas caused by outdated or inaccurate hydrographic data, dense vessel traffic, and the strategic or economic value of certain regions. This study aims to develop a multi-criteria decision-making model to determine national hydrographic survey priorities more efficiently and adaptively, in accordance with Indonesia’s complex maritime geography. The analysis results indicate that Navigational Safety (0.47) and Data Quality (0.35) are the most dominant criteria influencing survey prioritization. Sub-criteria such as Traffic Volume (0.32), Bathymetric Conditions (0.17), and CATZOC (Category Zone of Confidence) (0.14) serve as key indicators in the decision-making process. Areas such as the Indonesian Archipelagic Sea Lanes (ALKI) (0.26), Strategic Straits (0.15), and Strategic Ports (0.12) are identified as top priorities for survey implementation. These findings suggest that a risk-based and geospatial data-integrated approach provides a strong foundation for designing more targeted and impactful hydrographic survey policies. The study recommends several strategies, including enhancing the resolution and coverage of nautical charts, developing a national geospatial hydrographic information system, and utilizing modern survey technologies such as autonomous survey vessels and satellite data integration. Accordingly, this assessment model is expected to strengthen institutional capacity in supporting maritime safety, optimizing marine spatial planning, and promoting sustainable management of Indonesia’s vast and dynamic maritime domain.